Electrically Conductive Polyaniline-Coated Electrospun Poly(Vinylidene Fluoride) Mats - Merlini, Claudia; Barra, Guilherme Mariz de Oliveira; Ramôa, Sílvia Daniela Araújo da Silva; Contri, Giseli; Almeida, Rosemeire dos Santos; d’Ávila, Marcos Akira; Soares, Bluma G. (Frontiers in Materials, 2015)
Electrically conductive polyaniline (PANI)-coated electrospun poly(vinylidene fluoride) (PVDF) mats were fabricated through aniline (ANI) oxidative polymerization on electrospun PVDF mats. The effect of polymerization condition on structure and property of PVDF/PANI mats was investigated. The electrical conductivity and PANI content enhanced significantly with increasing ANI concentration due to the formation of a conducting polymer layer that completely coated the PVDF fibers surface. The PANI deposition on the PVDF fibers surface increased the Young Modulus and the elongation at break reduced significantly. Attenuated Total Reflectance-Fourier Transform Infrared spectroscopy (ATR-FTIR) revealed that the electrospun PVDF and PVDF/PANI mats display a polymorph crystalline structure, with absorption bands associated to the β, α and γ phases.